From social theories to agri-food system transformation practice: Summary of findings presented in the Delhi conference 'From Research to Impact' - Leñero, Eva Marina Valencia; McGuire, Erin; Boa-Alvarado, María (CGIAR, 2023)
Despite the global commitment to sustainability outlined in the Sustainable Development Goals, our agri-food systems are far from being sustainable, resilient, and just. Social inclusion and environmental protection, which are essential pillars of sustainability, are currently lagging. Despite agri-food systems remaining a primary driver of environmental damage, there is still a global increase in undernourishment, according to the Global Hunger Index. This contributes to pushing the planetary boundaries out of a “safe” zone for humanity, as highlighted by the findings of Campbell and colleagues. For this reason, a group of women from different disciplines and countries collaborated to develop the “X Equity Principles for Societal Transformation” to address the social inclusion challenges of agri-food systems. We presented our results for discussion at the conference “From Research to Impact: Towards Just and Resilient Agri-Food Systems,” organized in New Delhi, India, from October 9th to October 12th, 2023, as part of the CGIAR GENDER Impact Platform activities. The paper abstract has been accepted and submitted to Agricultural Systems in 2023.